The fungicide propiconazole induces hepatic steatosis and activates PXR in a mouse model of diet-induced obesity - Attema, Brecht; Kummu, Outi; Krutáková, Mária; Pavek, Petr; Hakkola, Jukka; Hooiveld, Guido J E J; Kersten, Sander (Archives of toxicology, 2025)
Propiconazole is a triazole fungicide previously shown to induce triglyceride accumulation in human liver HepaRG cells, potentially via activation of the Pregnane X Receptor (PXR). However, whether propiconazole can disrupt hepatic and whole-body metabolism in vivo is currently unknown. Therefore, we aimed to examine the metabolic effects of propiconazole in the context of metabolic dysfunction-associated steatotic liver disease (MASLD), obesity, and insulin resistance. To this end, male C57BL/6J mice were fed a high-fat diet for 20 weeks. During the last 10 weeks, mice additionally received vehicle, 0.04, 30, or 100 mg/kg body weight (bw)/day propiconazole via oral gavage. High-dose propiconazole, but not low or intermediate dose, reduced body weight gain and adipose tissue weight in obese mice. Mice receiving high-dose propiconazole displayed improved glucose tolerance and reduced levels of plasma triglycerides and cholesterol. Propiconazole dose-dependently increased liver weight and triglyceride levels and at high dose caused signs of hepatic inflammation. RNA sequencing on the liver revealed that propiconazole mainly induced PXR target genes. At intermediate and high dose, propiconazole induced pathways related to cell-cell interactions and inflammation, while oxidative phosphorylation was repressed by propiconazole. Comparison of gene regulation in wildtype and PXR knockout primary hepatocytes as well as gene reporter assays confirmed the activation of PXR by propiconazole. All in all, our data underscore the capacity of propiconazole to activate PXR in the liver and thereby promote the development of hepatic steatosis in vivo.
Keywords: Insulin Resistance; Lipid metabolism; MASLD; Obesity; pregnanový X receptor; Pregnane X Receptor; vztah mezi dávkou a účinkem léčiva; triazoly; myši; dieta s vysokým obsahem tuků; Metabolism disrupting chemicals (MDCs); Dose-Response Relationship, Drug; Mice; obezita; inzulinová rezistence; Triglycerides; Disease Models, Animal; Propiconazole; ztučnělá játra; mužské pohlaví; Triazoles; zvířata; Fungicides, Industrial; játra; Mice, Inbred C57BL; Liver; Animals; Fatty Liver; Male; průmyslové fungicidy; triglyceridy; Nuclear receptors/PXR; modely nemocí na zvířatech; Diet, High-Fat; myši inbrední C57BL